2016
DOI: 10.1016/j.apsusc.2016.01.091
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of wear and corrosion resistance of beta titanium alloy by laser gas alloying with nitrogen

Abstract: The relatively high elastic modulus coupled with the presence of toxic vanadium (V) in Ti6Al4V alloy has long been a concern in orthopaedic applications. To solve the problem, a variety of non-toxic and low modulus beta-titanium (beta-Ti) alloys have been developed. Among the beta-Ti alloy family, the quaternary Ti-Nb-Zr-Ta (TNZT) alloys have received the highest attention as a promising replacement for Ti6Al4V due to their lower elastic modulus and outstanding long term stability against corrosion in biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(48 citation statements)
references
References 48 publications
2
46
0
Order By: Relevance
“…Figure 11 shows the XRD profile for the laser-treated and untreated surfaces. It is important to point out that the penetration depth of the radiation into the material surface is typically a few μm in the XRD measurement [27]. The penetration depth is between 0.8 and 1.9 μm in our XRD (refer to Section 2.3).…”
Section: Indentation Mark 1 Indentation Mark 2 Indentation Markmentioning
confidence: 96%
See 1 more Smart Citation
“…Figure 11 shows the XRD profile for the laser-treated and untreated surfaces. It is important to point out that the penetration depth of the radiation into the material surface is typically a few μm in the XRD measurement [27]. The penetration depth is between 0.8 and 1.9 μm in our XRD (refer to Section 2.3).…”
Section: Indentation Mark 1 Indentation Mark 2 Indentation Markmentioning
confidence: 96%
“…We have recently demonstrated that laser surface remelting (hereafter, called laser remelting) of metallic materials, for example titanium or titanium-based alloys, leads to a greatly enhanced wear-resistance [27,28]. Meanwhile, corresponding studies on CoCrMo surface are relatively rare.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, laser treatment escalates the adhesion strength between GO coating and the substrates, which enhances the barrier effect of the coating, and further improves the corrosion resistance of laser/GO-coated sample. In this view, Chan et al [49] indicated that a more protective oxide film with higher crystallinity can be obtained by laser surface treatment compared with the air-passivated oxide film formed on the untreated surface. The EDX analysis of GO-coated and laser/GO-coated samples showed that apart from the presence of the expected elements (Ti, Nb, Ca, P, O, and N), a large amount of carbon was also detected that is related to the presence of GO.…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…Another study [49] demonstrated that reduced graphene oxide reinforced composite coatings on copper substrate can increase the corrosion resistance. In addition, laser treatment escalates the adhesion strength between GO coating and the substrates, which enhances the barrier effect of the coating, and further improves the corrosion resistance of laser/GO-coated sample.…”
Section: Accepted Manuscriptmentioning
confidence: 97%
See 1 more Smart Citation